Was ist Orthotylus obsoletus Fieb. 1861? (Heteroptera: Miridae). - Wagner, Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1954)
Nomenclatural Acts obsoletus Fieber, 1861 (Orthotylus), Lectotype; syn. n. pro Orthotylus adenocarpi Perris, 1857